2006
DOI: 10.1111/j.1570-7458.2006.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed mating reduces fecundity of blackheaded fireworm, Rhopobota naevana, on cranberry

Abstract: This study examines the effects of delayed mating on two successive generations of blackheaded fireworm, Rhopobota naevana Hübner (Lepidoptera: Tortricidae), a pest of cranberry, Vaccinium macrocarpon Aiton (Ericaceae). The first (spring) generation produces eggs that hatch soon after oviposition, whereas the second (summer) generation produces mostly diapause eggs. Unmated female and male moths were placed together on the first, second, fourth, sixth, or eighth day after emergence. In the first generation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The negative effect of extended calling on the number of eggs laid by moths has been demonstrated previously by Harari et al ., while reduced fecundity with female age at mating has been demonstrated for L. botrana by Torres‐Vila et al . and for other species elsewhere . Jones and Aihara‐Sasaki have further suggested a synergetic effect on the decreased number of eggs when mating is delayed, as older females may die before ovipositing because of various mortality factors.…”
Section: Discussionmentioning
confidence: 66%
“…The negative effect of extended calling on the number of eggs laid by moths has been demonstrated previously by Harari et al ., while reduced fecundity with female age at mating has been demonstrated for L. botrana by Torres‐Vila et al . and for other species elsewhere . Jones and Aihara‐Sasaki have further suggested a synergetic effect on the decreased number of eggs when mating is delayed, as older females may die before ovipositing because of various mortality factors.…”
Section: Discussionmentioning
confidence: 66%
“…However, there are examples of successful mating disrup-tion programs for both univoltine and multivoltine moth species. Delayed mating can differentially affect different generations within bivoltine and multivoltine species (Fitzpatrick, 2006). As well, the multivoltine codling moth, C. pomonella, is effectively controlled with mating disruption in many temperate fruit growing regions (Kehat et al, 1995;Brunner et al, 2002).…”
Section: Voltinismmentioning
confidence: 99%
“…In British Columbia, Canada, each generation of the bivoltine blackheaded fireworm, Rhopobota naevana Hübner (Lepidoptera: Tortricidae), is affected differently by delayed mating (Fitzpatrick, 2006). Assessment of the effect of delayed mating on moth fitness in different families or with different life-history traits, such as voltinism, larval diet breadth, dispersal capacity, female mating strategy, and egg development strategy, will provide more information on how to best implement mating disruption into IPM programs that target different species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some situations, mating disruption does not completely inhibit mating because some males may eventually Þnd females if given enough time (Torres-Vila et al 2002, Wenninger andAverill 2006). Nevertheless, several laboratory studies have shown that delayed mating can have a signiÞcantly negative effect on the reproductive performance of lepidopteran pests by decreasing female readiness to mate, and reducing the number of eggs laid and the hatchability (Torres-Vila et al 2002, Michereff et al 2004, Fitzpatrick 2006. Thus, even though mating disruption treatment may not inhibit mating completely, signiÞcant control of the pest population may be achieved through delayed mating (Miller et al 2006).…”
mentioning
confidence: 97%